2000
DOI: 10.1130/0091-7613(2000)28<607:aoadsc>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Autopsy on a dead spreading center: The Phoenix Ridge, Drake Passage, Antarctica

Abstract: New bathymetric and magnetic anomaly data from the Phoenix Ridge, Antarctica, show that extinction of all three remaining segments occurred at the time of magnetic chron C2A (3.3 ± 0.2 Ma), synchronous with a ridge-trench collision south of the Hero Fracture Zone. This implies that the ultimate cause of extinction was a change in plate boundary forces occasioned by this collision. Spreading rates slowed abruptly at the time of chron C4 (7.8 ± 0.3 Ma), probably as a result of extinction of the West Scotia Ridge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 19 publications
0
87
0
1
Order By: Relevance
“…All this time, and afterwards, accretion continued at the Antarctic-Phoenix Ridge, and the Phoenix plate continued to be subducted beneath the Antarctic Peninsula (Larter and Barker, 1991;Livermore et al, 2000;Eagles, 2003). This situation inevitably led to further ridge crest-trench collisions like those described southwest of the Tula Fracture Zone, but because of the long-offset on the Tula transform fault the first of these later collisions dates from around 20 Ma (Fig.…”
Section: Slab Windows Beneath Cape Horn and North Of The Tula Fracturmentioning
confidence: 99%
“…All this time, and afterwards, accretion continued at the Antarctic-Phoenix Ridge, and the Phoenix plate continued to be subducted beneath the Antarctic Peninsula (Larter and Barker, 1991;Livermore et al, 2000;Eagles, 2003). This situation inevitably led to further ridge crest-trench collisions like those described southwest of the Tula Fracture Zone, but because of the long-offset on the Tula transform fault the first of these later collisions dates from around 20 Ma (Fig.…”
Section: Slab Windows Beneath Cape Horn and North Of The Tula Fracturmentioning
confidence: 99%
“…The last collisions occurred at V62 ‡S^63 ‡S on the margin around chron C3A (V6.5 Ma) [1]. Spreading on the Antarctic^Phoenix Ridge stopped around anomaly C2A (V3.3 Ma) [2], leaving only a small remnant of the Phoenix plate unsubducted, and this remnant was incorporated into the Antarctic plate.…”
Section: Tectonic Settingmentioning
confidence: 99%
“…The Phoenix plate has been treated in the past as a laboratory for the study of plate tectonic driving forces [1] via the study of sea£oor spreading rate changes revealed in magnetic anomaly pro¢les [1,2]. An inversion that ¢ts conjugate magnetic anomaly identi¢cations together is a powerful technique to identify discrepancies in identi¢cations of anomalies on pro¢les and generate estimates of spreading rates.…”
Section: Introductionmentioning
confidence: 99%
“…Its interpretation as an extinct, buried spreading centre was con¢rmed by seismic pro¢ling (King et al, 1997). Although this generally has the character of a typical median valley, some pro¢les reveal the existence of basement highs of limited extent (King et al, 1997), which may represent late-stage eruptions rather like those inferred on segment P2 of the extinct Phoenix Ridge, southwest of the Shackleton Fracture Zone (Livermore et al, 2000). The ridge axis, as de¢ned by the gravity low, is linear, with no large o¡sets, although a small discontinuity at 62 ‡20PS, 49 ‡50PW is evident.…”
Section: Constraintsmentioning
confidence: 99%